1993
DOI: 10.1128/jb.175.24.7968-7975.1993
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional analysis of the Aeromonas salmonicida S-layer protein gene vapA

Abstract: The vapA gene of Aeromonas salmonicida encodes the subunit of the surface protein array known as A-layer. Nucleotide sequence analysis of the 374 bp of DNA immediately upstream of vapA revealed two potential promoter sequences and other possible regulatory sequences. Sequencing and polymerase chain reaction analysis showed that the region was conserved in wild-type A. salmonicida. Primer extension and Northern (RNA) blot analysis showed that vapA transcription in A. salmonicida was directed predominantly by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…The half-life of the S-protein mRNAs has only been determined for three species, Caulobacter crescentus (10 to 15 min; Fisher et al, 1988), A. salmonicida (22 min;Chu et al, 1993), and L. acidophilus (15 min;Boot et al, 1996a). Secondary-structure formation in the long, untranslated leader sequences, found for many S-protein mRNAs (Table 1) …”
Section: Expression Of S-protein Genesmentioning
confidence: 99%
“…The half-life of the S-protein mRNAs has only been determined for three species, Caulobacter crescentus (10 to 15 min; Fisher et al, 1988), A. salmonicida (22 min;Chu et al, 1993), and L. acidophilus (15 min;Boot et al, 1996a). Secondary-structure formation in the long, untranslated leader sequences, found for many S-protein mRNAs (Table 1) …”
Section: Expression Of S-protein Genesmentioning
confidence: 99%
“…1, Spots 1 -5, 37 and 38). It has been estimated that in order to cover its entire surface with the VapA protein, A. salmonicida needs to synthesize approximately 5000 copies of the VapA protein per second (Chu et al 1993). The precise nature of the multiple isoelectropherotypes of the VapA protein in A. salmonicida has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, similar translational regulatory mechanisms could also exist for these genes. In addition to this function, these 5ЈUTR of the S-layer protein mRNAs could also be implicated in the stability of their transcripts (Fisher et al, 1988;Chu et al, 1993;, as has been demonstrated for the E. coli OmpA mRNA (Melefors and Gabian, 1988). These two mechanisms would help to explain the fast regeneration of the S-layer observed under some experimental conditions (Lortal et al, 1992;Firtel et al, 1995).…”
Section: јUtr Mrna Binding By Slpa and Translational Autoregulationmentioning
confidence: 97%